Desain Dan Analisa Mekatronika Robot Fire Fighting - Hardianto, Muh. Syukri; Ganda Isnuardana; M. Ibnu Fajar Al-Afghani; Oscar Haris (Universitas Nusa Putra, 2021)
This research was made as a refinement of various research on fire fighting robots, which in this research emphasizes the value of improvement from electronic and mechanical designs, this robot is not controlled by anything either by remote control or by joystick, this robot moves itself from the truck. fire extinguisher to extinguish the fire based on the sensitivity of the existing sensor in detecting the presence of a fire point, as well as the navigation system that the robot has in the form of a proximity sensor, this sensor keeps the robot able to move without obstacles in the form of walls or other objects that block the robot's pace. . In this research analysis and calculations will be carried out about the design of the equipment that will be needed. The data used are data sourced from primary or secondary data from available data from several manufacturers of the equipment needed. Based on the data analysis carried out, it can be concluded that the robot equipment from time to time will continue to experience changes and / or improvements.